Dose-dependent anti-inflammatory effect of inhaled mometasone furoate/formoterol in subjects with asthma. - Nolte, H; Pavord, I; Backer, V; Spector, S; Shekar, T; Gates, D; Nair, P; Hargreave, F (2013)
OBJECTIVE: A well-controlled study in patients with allergic asthma was warranted to assess dose-dependency between fractional concentration of exhaled nitric oxide (FeNO) and sputum eosinophils to a combination of an inhaled corticosteroid plus a long-acting β2-agonist. We sought to characterize the dose-dependency of mometasone furoate/formoterol (MF/F) using FeNO and sputum eosinophil percentage as surrogates of airway inflammation in subjects with allergic asthma. METHODS: Following a 2-week, open-label run-in, 93 subjects (≥12 y) using only short-acting beta agonist reliever medication as needed, were randomized to twice daily (BID) placebo; MF/F 100/10 μg, 200/10 μg, or 400/10 μg (via pressurized metered-dose inhaler [MDI]); MF-MDI 200 μg; or MF 200 μg via dry powder inhaler (DPI) during a 2-week, double-blind treatment period. RESULTS: All active treatments demonstrated significant percentage reductions from baseline in FeNO compared with placebo at all time points (P ≤ 0.034). At endpoint, mean MF/F treatment group FeNO reductions ranged from -35.3% to -61.4%. Sputum eosinophil percentage reductions from baseline were significant compared with placebo for the MF/F 200/10 μg, MF/F 400/10 μg, and MF-DPI 200 μg groups at endpoint (P ≤ 0.023). Escalating MF/F doses significantly reduced both FeNO (P ≤ 0.001) and sputum eosinophil (P ≤ 0.022) levels in a dose-dependent manner at all time points. All treatments were well tolerated; no serious adverse events were observed. CONCLUSION: All 3 MF/F doses demonstrated pronounced, clinically meaningful, dose-dependent reductions in FeNO, with reduced sputum eosinophil levels for MF/F 200/10 μg and MF/F 400/10 μg. These findings suggest both inflammatory markers may be useful in assessing corticosteroid responsiveness in asthma patients, and perhaps identifying the same asthma subphenotype. Clinical Trials.gov: NCT00635882.